2008
DOI: 10.1002/ijc.23986
|View full text |Cite
|
Sign up to set email alerts
|

Cure of established GL261 mouse gliomas after combined immunotherapy with GM‐CSF and IFNγ is mediated by both CD8+ and CD4+ T‐cells

Abstract: We were the first to demonstrate that combined immunotherapy with GM-CSF producing GL261 cells and recombinant IFNc of preestablished GL261 gliomas could cure 90% of immunized mice. To extend these findings and to uncover the underlying mechanisms, the ensuing experiments were undertaken. We hypothesized that immunizations combining both GM-CSF and IFNc systemically would increase the number of immature myeloid cells, which then would mature and differentiate into dendritic cells (DCs) and macrophages, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
(73 reference statements)
1
22
0
Order By: Relevance
“…Other studies examining immunotherapy in murine CNS tumor models have also found a similar dependence on the CD8 population (19). Smith et al (19) found that both CD4 and CD8 cells were essential for the combined immunologic effect of GM-CSF and IFN-γ against intracranial GL261 mouse gliomas.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Other studies examining immunotherapy in murine CNS tumor models have also found a similar dependence on the CD8 population (19). Smith et al (19) found that both CD4 and CD8 cells were essential for the combined immunologic effect of GM-CSF and IFN-γ against intracranial GL261 mouse gliomas.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies examining immunotherapy in murine CNS tumor models have also found a similar dependence on the CD8 population (19). Smith et al (19) found that both CD4 and CD8 cells were essential for the combined immunologic effect of GM-CSF and IFN-γ against intracranial GL261 mouse gliomas. However, in our study, CD4-depleted mice still derived a survival benefit with the addition of PD-1 blockade to radiation, but the survival improvement was not as robust as in wild-type mice.…”
Section: Discussionmentioning
confidence: 61%
“…However, the downregulation of IFNg secretion in both cell lines after irradiation implies that the major effect of IFNg transfected tumor cells is intrinsic. 19 Apoptosis occurs in a variety of cell types, including tumor cells, after radiation. 20,21 An irradiation dose of 20 Gy was necessary to fully prevent the formation of new tumor cell clones in the standard clonogenic assay but the cells were irradiated with 80 Gy before immunizations, as the cell numbers were much higher than in the clonogenic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an even much more individualized, targeted approach was developed which is immunotherapy by vaccination with dendritic cells after ex vivo stimulation and pulsing with autologous tumor antigens [53,54]. This is, indeed, by itself a completely individualized therapy: for each patient, a completely different vaccine is produced [53].…”
Section: Immune Therapymentioning
confidence: 99%
“…This is, indeed, by itself a completely individualized therapy: for each patient, a completely different vaccine is produced [53]. Being robust and simple, on the one hand, it has proven to be quite successful on the other, and might thus give an indication in which way to develop future strategies in the difficult field of glioblastoma therapy.…”
Section: Immune Therapymentioning
confidence: 99%